Histological Grading of Hepatocellular Carcinoma—A Systematic Review of Literature - Martins-Filho, Sebastiao N.; Paiva, Caterina; Azevedo, Raymundo Soares; Alves, Venancio Avancini Ferreira (Frontiers in Medicine, 2017)
Background: Histological grading typically reflects the biological behavior of solid tumors, thus providing valuable prognostic information. This is also expected in Hepatocellular Carcinoma (HCC), although limited access to biopsy samples and a lack of standardization might hinder its full predictive value in this cancer. Objectives: In order to better understand the current practices of histological grading in HCC, we examined the latest publications addressing its impact on the outcome of patients following surgical treatment. Methods: We searched the PubMed (MEDLINE) database under the headings “hepatocellular carcinoma”, “grade OR grading”, and “prognosis”. Qualitative and quantitative assessment of publications was performed according to the reference they used to grade their tumors (e.g. Edmondson-Steiner, World Health Organization). Results: We reviewed a total of 216 articles: 114 enclosed adequate information and were included herein. Among those, we found divergences as well as inaccuracies in the histological grade assessment of this cancer, which might have led to a non-standardized grade distribution, with further impact on data analysis. Nevertheless, in most of them, poor tumor differentiation correlated with worse prognosis, expressed by lower overall and/or disease-free survival. Conclusions: While histological grading of HCC has an important prognostic role, there is an unsatisfactory heterogeneity on the microscopic assessment of this tumor, urging for a movement towards standardization.